NILAI-NILAI PENDIDIKAN DALAM KELOMPOK SEBAYA - GUSTINA GUSTINA (Ta'dib, 2014)
A group of the same age was the second environment for specific individu in interacting with others in his/her environment. It became an intercation medium by this group to explore their knowledge. In real life, it usually took much influence on students’ attitude rather than parents’ influence. The group might play an important role on one’s characteristic such as way of thinking, knowledge, understanding, attitude, interest, hobby, wish, performance, and behaviour in daily activities. Therefore, educational value had to be kept and developed in this group was as follows: the value of honest, initiative, responsibility, groupwork, wanting to share, respectfulness,discipline, and so on.Kata kunci: nilai pendidikan, kelompok sebaya